Hubungan Kualitas Air Sumur dengan Kejadian Diare di Daerah Aliran Sungai (DAS) Bengawan Solo - Yuniarno, Saudin; Sulistiyani, Sulistiyani; Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Background: Water has a role as media of many infectious diseases. One of disease whisch is often transmitted through water is diarrhea. The quality of water consumed by the community must be fillfull for health. So, It becomes the important thing in preventing the incidence of diarrhea.  The aim of this research was to determine the relationship between the quality of well water and the incidence of diarrhea on the community living along the riverside area of Bengawan Solo. Method: This was an observational research using cross sectional design. The subjects of this research were 66 persons staying for each upstream and downstream of Bengawan Solo.The quality of well water was assessed based on the parameters for temperature, pH, Biochemical Oxygen Demand (BOD), total dissolved solid (TDS), and E. coli.  The occurrence of diarrhea was determined by interviewing. Data would be analyzed using chi-square test at 0,05 level of significance. Result: The result of this research showed that variables which had relationship (p-value<0,05) to the incidence of diarrhea were: education, income, distance of well to septictank and to river,  knowledge, attitude, practice, pH, BOD, TDS, and E. coli content.  Well water located on upstream area of Bengawan Solo containing E. coli. Person who had well water containing  E. coli  over standard had 0,17 of probability to suffer diarrhea.  The other one, well water located on downstream area of Bengawan Solo containing total dissolved solid.  Person who had well water containing E. coli and TDS over standard had 0,13 of probability to suffer diarrhea. Conclusion: well water containing E. coli is the main variable associated to the occurrence of diarrhea on upstream area of Bengawan. The content of E. coli and TDS are two variables associated to the occurrence of diarrhea on downstream area of Bengawan. Key words :   Quality of well water, Diarrhea  Incidence, community living on the riverside of Bengawan Solo.